New approaches for cofactor recycling: application to chemical synthesis and electrochemical devices - Reeve, H (2015)
The work in this Thesis addresses the challenges associated with using redox enzymes for chemical synthesis. The use of enzymes as catalysts in the synthesis of fine chemicals is becoming more wide spread, in part due their ability to catalyse reactions with incredible selectivity under relatively mild conditions. In particular, enzymes are useful for selective reduction of ketones to enantiomerically pure alcohols or amines, and partial oxidations of alkanes to alcohols. However, a key limitation to exploiting redox enzymes in these reaction pathways is the requirement for a specialised electron source, usually the expensive nicotinamide cofactors NADH or NADPH. Existing cofactor regeneration methods use a second enzyme with a sacrificial substrate which is oxidised to generate a stoichiometric waste product; this complicates isolation of the desired product and prevents the environmental benefits of biocatalysis from being fully realised. In order to provide clean and efficient biocatalytic routes, improved recycling methods for these cofactors are crucial. This Thesis develops two novel methods for in situ cofactor recycling. The first is an electro-enzymatic system; an NAD+-reductase enzyme is shown to use electrons directly from an electrode for supply of NADH to a co-immobilised cofactor-dependent enzyme. The second uses a hydrogenase, NAD+ reductase and cofactor-dependent enzyme immobilised on conducting particles for H2-driven NADH regeneration. This relies on the thermodynamically favourable reduction of NAD+ by H2 when the hydrogenase and NAD+-reductase are in electronic contact, provided by the conducting particle. The electro-enzymatic approach to NAD+ reduction is then adapted for electrochemical devices; an enzyme catalysed fuel cell and a self-powered biosensor were considered.